'It's not like it used to be': Respect and nostalgia in the policing of nightlife. Issue 2 (June 2019) - Wadds, Phillip
Contemporary debates regarding criminal justice, law and order, and also the occupational consciousness of policing itself, are often concerned with a mythical period of heightened 'respect' for authority that is contrasted with the decline of such respect in contemporary work patterns and interaction with the public. This nostalgia features most prominently in discussions about spaces and work practices where officers feel threatened, challenged or 'under-siege'. One such site is the night-time economy, where expansion of drinking-based leisure and a long-term liberalisation of regulatory controls have exerted more pressure on police and produced urban spaces where this 'lack of respect' is keenly felt. This paper analyses themes that emerged from 15 interviews conducted with current and former members of the New South Wales Police Force to argue that the emergence and growth of urban nightlife have played a key role in promoting a nostalgic discourse that reflects ambivalence about historical efforts to lift police–community relations and the more formal regulation of interaction with the public. Such nostalgia also serves as a personal, social and existential resource that helps fortify shared meaning and a sense of solidarity in the working lives of officers.